Adhesion between zirconia and resin cement: A critical evaluation of testing methodologies - GRS, Lopes [UNESP]; NC, Ramos [UNESP]; Grangeiro, M. T.V. [UNESP]; JDM, Matos [UNESP]; Bottino, M. A. [UNESP]; M, Özcan; LF, Valandro; RM, Melo [UNESP] (Elsevier, 2021)
This study aimed to analyze different methodologies (tensile, microtensile, shear, microshear, and interfacial toughness) for evaluation of the bond strength between zirconia (Y-TZP) and resin cement. Zirconia ceramic blocks (VITA in-Ceram® YZ, VITA Zahnfabrik, Germany) were obtained, substrate surfaces were air-abraded with aluminum oxide (50 μm) for 10 s (2 bar pressure, distance: 10 mm, angle: 90°). Then, the specimens were washed with distilled water, dried, and coated with Clearfil Ceramic Primer that was actively applied with a microbrush for 20 s. The specimens were then cemented with resin cement under a load of 750 g, followed by photo-polymerization (40 s on each surface). After cementation, the specimens were aged in thermocycling (8000 cycles, 5–55 °C, 30 s for each bath) and subjected to tensile, microtensile, shear, microshear or interfacial toughness tests. All specimens were inspected for failure modes. The microtensile test showed the highest bond value (18.29 N/mm2). The microshear tests showed the highest coefficient of variation (0.59) and highest number of pre-test failures. The interfacial energy to fracture test showed that as the shear stress increased its interaction in the adhesive interface, the coefficient of variation also increased. The bond strength of Y-TZP showed different results according to the methodology, as well as its interfacial energy to fracture varied according to the angulation/type of stress specimen was submitted. The lower the shear stress at the adhesive interface of the mixed tests (interfacial energy to fracture), the lower was the variability of the test.
Keywords: Adhesion; Ceramics; Fracture mechanics; Fracture strength; Mechanical test; Shear bond strength; Tensile bond strength; Y-TZP; Zirconia